Bisphosphonates or RANK‐ligand‐inhibitors for men with prostate cancer and bone metastases: a Cochrane Review and network meta‐analysis - Tesfamariam, Yonas Mehari (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of bisphosphonates and RANK‐ligand (RANKL)‐inhibitors for supportive treatment in prostate cancer with bone metastases and to generate a clinically meaningful treatment ranking according to their safety and efficacy.